Protection against Pertussis in Humans Correlates to Elevated Serum Antibodies and Memory B Cells - Marcellini, Valentina; Piano Mortari, Eva; Fedele, Giorgio; Gesualdo, Francesco; Pandolfi, Elisabetta; Midulla, Fabio; Leone, Pasqualina; Stefanelli, Paola; Tozzi, Alberto Eugenio; Carsetti, Rita; , The Pertussis Study Group; Agricola, E.; et al. (Frontiers in Immunology, 2017)
Pertussis is a respiratory infection caused by Bordetella pertussis that may be particularly severe and even lethal in the first months of life when infants are still too young to be vaccinated. Adults and adolescents experience mild symptoms and are the source of infection for neonates. Adoptive maternal immunity does not prevent pertussis in the neonate. We compared the specific immune response of mothers of neonates diagnosed with pertussis and mothers of control children. We show that women have pre-existing pertussis-specific antibodies and memory B cells, and react against the infection with a recall response increasing the levels specific serum IgG, milk IgA and the frequency of memory B cells of all isotypes. Thus, the maternal immune system is activated in response to pertussis and effectively prevents the disease indicating that the low levels of pre-formed serum antibodies are insufficient for protection. For this reason memory B cells play a major role in the adult defense. The results of this study suggest that new strategies for vaccine design should aim at increasing long-lived plasma cells and their antibodies.